2020
DOI: 10.1111/are.14612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on immune responses and carbohydrate metabolism in the Chinese mitten crab, Eriocheir sinensis

Abstract: In aquaculture, hypoxia is an important stressor that can inhibit the healthy development of Chinese mitten crab, Eriocheir sinensis. The aim of this work was to research on how hypoxia (1 mg/L) followed by reoxygenation affects the immune response and carbohydrate metabolism in the Chinese mitten crab. The activities of immune‐related enzymes including lysozyme (LZM), acid phosphatase (ACP), alkaline phosphatase (AKP), superoxide dismutase (SOD) and phenoloxidase (PO) and concentration changes in haemolymph g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…sapidus 81 and Chinese mitten crab E . sinensis 82 have reported that hypoxia caused reductions in LZM and PO activities and attendant suppression of immune responses. Further, production and release of haemocytes into the haemolymph is known to be an innate immune response in crustaceans 83 .…”
Section: Effects Of Hypoxia On the Innate Immunty In Crustaceanmentioning
confidence: 99%
“…sapidus 81 and Chinese mitten crab E . sinensis 82 have reported that hypoxia caused reductions in LZM and PO activities and attendant suppression of immune responses. Further, production and release of haemocytes into the haemolymph is known to be an innate immune response in crustaceans 83 .…”
Section: Effects Of Hypoxia On the Innate Immunty In Crustaceanmentioning
confidence: 99%
“…The Chinese mitten crab is one of the most important aquaculture species in China because of its economic and ecological roles (Gao et al, 2018). It is produced in aquaculture yielding 750,000 tonnes per year, exceeding 7.5 billion USD value in 2017 (Bao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese mitten crab is one of the most important aquaculture species in China because of its economic and ecological roles (Gao et al, 2018). It is produced in aquaculture yielding 750,000 tonnes per year, exceeding 7.5 billion USD value in 2017 (Bao et al, 2020). Due to the substantial economic benefits, the culture density of Chinese mitten crab in rearing ponds has gradually increased every year (Bao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the respiration metabolism of aquatic organisms would directly affect the water-air interface CO 2 fluxes. As known, some biotic and abiotic stresses are able to change the rates of respiratory metabolism of many aquatic vertebrates and invertebrates, such as osteichthyes (Liu et al, 2016), echinoderms (Bai et al, 2015;Kühnhold et al, 2017;Sin et al, 2019), crustaceans (Fernańdez-Cisnal et al, 2018;Bao et al, 2020;Ulaje et al, 2020) and molluscans (Haure et al, 2003;Romo et al, 2009). Oxygen consumption rate is generally worked as an important indicator to assess their respiratory and metabolic status.…”
Section: Introductionmentioning
confidence: 99%